Ecology of Bats, Their Ectoparasites, and Associated Pathogens on Saint Kitts Island. Issue 5 (9th June 2016) - Reeves, Will K.; Beck, Jason; Orlova, Maria V.; Daly, Jennifer L.; Pippin, Kristi; Revan, Floyd; Loftis, Amanda D.
Abstract: Ectoparasites of bats and bat-associated pathogens are poorly studied in the Lesser Antilles Islands. We report on an 11-mo field study on Saint Kitts Island of bat populations, their associated ectoparasites, and pathogens. We report on five ectoparasite species, including four Streblidae (Diptera) and a Spinturnicidae (Acari). Several genotypes of unnamed Bartonella were isolated from bats and ectoparasites. Microfilaria of an undetermined Litomosoides spp. were detected in blood from Artibeus jamaicensis Leach (Chiroptera: Phyllostomidae) (and associated ectoparasites: Trichobius intermedius Peterson and Hurka (Diptera: Streblidae) and Periglischrus iheringi Oudemans (Acari: Spinturnicidae)). In addition, an Ehrlichia sp. and Rickettsia africae were detected in the blood of several bat species. Our study is one of the first surveys of ectoparasite-borne pathogens in wild mammals from St. Kitts.